2009
DOI: 10.1155/2009/178751
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Virtual Reality Immersion and Audiovisual Distraction Techniques for Patients with Pruritus

Abstract: VRI and AVD techniques demonstrated the ability to diminish itching sensations temporarily. Further studies on the immediate and late effects of interactive computer distraction techniques to interrupt itching episodes will open potential paths for future pruritus research.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
38
1
2

Year Published

2011
2011
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 53 publications
(46 citation statements)
references
References 24 publications
5
38
1
2
Order By: Relevance
“…However, there was no significant gain in using an HMD with head tracking compared to projecting the interactive game environment onto a blank wall. These data are consistent with recent findings that HMDs do not offer an analgesic advantage over other interactive audiovisual environments (Dahlquist, et al, 2010;Leibovici, et al, 2009;Wender, et al, 2009). The present data also extend these findings in two key ways, which are elaborated below.…”
Section: Discussionsupporting
confidence: 93%
“…However, there was no significant gain in using an HMD with head tracking compared to projecting the interactive game environment onto a blank wall. These data are consistent with recent findings that HMDs do not offer an analgesic advantage over other interactive audiovisual environments (Dahlquist, et al, 2010;Leibovici, et al, 2009;Wender, et al, 2009). The present data also extend these findings in two key ways, which are elaborated below.…”
Section: Discussionsupporting
confidence: 93%
“…84,85) distraction with noncontact stimulation also inhibits itching in humans 86) and scratching behaviors in mice. 87,88) These findings suggest the presence of itch-inhibitory systems in the central nervous system.…”
Section: Itch-inhibitory Systemmentioning
confidence: 95%
“…One past study conducted in Israel investigated the impact of VR on itching caused by atopic dermatitis and psoriasis vulgaris. In this study data were gathered on the impact during a VR session and ten minutes afterwards [21]. This study found that VR significantly decreased itching during the VR sessions and also at ten minutes afterwards.…”
Section: Introductionmentioning
confidence: 99%